Fundamentals of biochemistry - Voet, Donald
Voet and Pratt's 4th edition of Principles of Biochemistry, challenges readers to better understand the chemistry behind the biological structure and reactions occurring in living systems. The latest edition continues this tradition, and additionally incorporates coverage of recent research and an expanded focus on preparing and supporting students throughout the course. With the addition of new conceptual assessment content to WileyPLUS, providing the opportunity to assess conceptual understanding of key introductory biochemistry concepts and retrain themselves on their misconceptions